Co-creative media innovation to promote OTOP Nawatwithi community-based tourism: a case of Ban-klongyong, Salaya Sub-district, Phuttamonthon Sub District, Nakhon Pathom Province - Saengduangdee et al., Vichet (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The research article has main objective to develop co-creative media innovation to promote OTOP Nawatwithi community-based tourism of Ban-klongyong, Salaya Sub-district, Phuttamonthon District, Nakhon Pathom Province. The Qualitative research based method; documentary analysis, observation, interviews and community forum with community leaders, communities of OTOP Nawatwithi community based-tourism, community products traders and community people, was applied to develop co creative media that can promote community-based tourism. The common theme analysis was brought to analyze qualitative data derived. The study find that stakeholders involved and community people of Ban Klong Yong agree to use community logo and slogan presented by buffalo cartoon mascot together with slogan “Monrak Thung Klong Yong” to develop 7 prototypes of creative media innovation enable to convey meaning, perception, and retention of Ban Klong Yong identity value which is differentiate than others, and that can promote the sustainable management of Ban Klong Yong OTOP Nawatwithi community-based tourism as wish; mascot standy, a tourist map which shows all 15 tourist attraction of Ban Klong Yong, a map of Ban Klong Yong route, poster, folder, line stickers, and miscellaneous media especially for souvenirs. Article history : Received 10 December 2019 Revised 1 April 2020 Accepted 4 April 2020 SIMILARITY INDEX = 0.00 %